Lavoisiereae (Melastomataceae) from Serra da Canastra National Park, Minas Gerais, Brazil, with two new species - Ferreira-Alves, Rodolfo; Romero, Rosana (Phytotaxa, 2025)
The current study cataloged 26 species of the Lavoisiereae tribe (Melatomataceae) in the Serra da Canastra National Park (SCNP), located in the southwest of the state of Minas Gerais, Brazil. The most representative genus is Microlicia, which comprises 24 species, followed by Rhynchanthera, with two species. An identification key for the species, morphological descriptions, taxonomic notes, geographical distribution, habitat information, and data on flowering and fruiting are provided. Additionally, Microlicia nakajimae and Microlicia sanfranciscana, endemic to the SCNP, are described and compared with similar morphologically species. Rhynchanthera dichotoma is cited for the first time in the SCNP.